Áhrif nýskógræktar á kolefnisbindingu í jarðvegi á Íslandi - Joel Charles Owona 1978- (2019)
Afforestation does not only establish new forests on treeless lands, but also changes many other aspects of the ecosystem, including the fauna, ground vegetation and soil properties. One of the most important ecosystem changes is the influence on the ecosystem carbon (C) stocks in different aboveground and belowground C pools. If afforestation is to be used as a method to sequester atmospheric carbon dioxide (CO2), to mitigate climate warming, it is important not only to consider changes in aboveground tree biomass, but also in the other four major ecosystem pools (dead wood, ground vegetation, litter layer and soil organic carbon (SOC)). The true CO2 mitigating potential of afforestation is the net change in all those five pools, but especially the last two pools have often been neglected in prior studies. Here I present a study of three afforestation sites in SW Iceland named Heiðmörk, Nesjavellir and Ölfusvatn forests. Heiðmörk is the largest site, planted with different coniferous tree species since ca. 1950 and also contains large naturally regenerated (self-seeded) areas of the native downy birch (Betula pubesecens). The Nesjavellir and Ölfusvatn forests are younger, since ca. 1997, and the former has planted stands of both birch or conifers and also some naturally regenerated areas self-seeded from local birch forest remnant, while the latter only has planted stands of either birch or conifers. To examine the influences of afforestation: i) between sites, ii) between different forest types and iii) with respect to increasing forest age, the present study compared different ecosystem properties of adjacent treeless control sites with afforested areas. The ecosystem properties included: i) ground vegetation cover, composition and biomass, ii) soil physical properties (bulk density stoniness, soil and litter depths as well as soil and litter dry mass), iii) soil chemical properties (pH, SOC and N concentration in different soil layers, C/N ratio in both soils and litter) and iv) ecosystem C stocks (soils, ...